Approach to Bourdieu's concepts of countryside, habitus, capital and symbolic violence - Vargas Huanca, Georgette (2021)
In this text the author analyzes Pierre Bourdieu's concepts of field, habitus, capital and symbolic violence in order to explain one's own disposition to accept "the order of things" based on the consideration of the game of roles that are assumed as "natural". It is considered that these concepts are constitutive to approach Bourdieu's theoretical approach and to carry out an analysis of social behavior. In the article, through a bibliographic analysis of various specialist sources and the author himself, reflections on the scope of these concepts and their application to various aspects of reality are presented.